2020
DOI: 10.1101/2020.06.01.127340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harnessing Ultrasound-Stimulated Phase Change Contrast Agents to Improve Antibiotic Efficacy Against Methicillin-ResistantStaphylococcus aureusBiofilms

Abstract: 17Bacterial biofilms, often associated with chronic infections, respond poorly to antibiotic 18 therapy and frequently require surgical intervention. Biofilms harbor persister cells, metabolically 19 indolent cells, which are tolerant to most conventional antibiotics. In addition, the biofilm matrix 20 can act as a physical barrier, impeding diffusion of antibiotics. Novel therapeutic approaches 21 frequently improve biofilm killing, but usually fail to achieve eradication. Failure to eradicate the 22 biofilm … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 58 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…32,33 Similarly, a limited number of studies have demonstrated increased antibiotic efficacy against infections using therapeutic ultrasound. [34][35][36][37] Increased cytotoxicity is likely due to increased cell uptake of drug in response to ultrasound-induced increases in cell membrane permeability. 33,34,38 However, augmenting drug delivery via ultrasound insonation is typically more efficacious when combined with microbubble-based ultrasound contrast agents (UCA) (Fig.…”
Section: Basics Of Ultrasound Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Similarly, a limited number of studies have demonstrated increased antibiotic efficacy against infections using therapeutic ultrasound. [34][35][36][37] Increased cytotoxicity is likely due to increased cell uptake of drug in response to ultrasound-induced increases in cell membrane permeability. 33,34,38 However, augmenting drug delivery via ultrasound insonation is typically more efficacious when combined with microbubble-based ultrasound contrast agents (UCA) (Fig.…”
Section: Basics Of Ultrasound Physicsmentioning
confidence: 99%
“…Other phase-change contrast agents (typically liquid PFC droplet stabilized by a phospholipid shell) with 100-400 nm diameters have also been used to enhance antibiotic efficacy against biofilms by up to 94%. 37 Rapoport et al describe development of ultrasound-activated, paclitaxel-carrying, PEG-PLLA nanoemulsions that convert into microbubbles upon insonation (1 MHz, 3.4 W cm À2 ) for cancer treatment. This ultrasound-triggered nanotherapy causes tumor regression by an order of magnitude in ovarian, breast, and orthotopic pancreatic cancer mouse models.…”
Section: Reviewmentioning
confidence: 99%
“…A disadvantage of microbubbles is their short half-life following injection and their relatively large size (1 to 4 mm in diameter) (106), which may hamper penetration into biofilms. Maintaining microbubbles in the more stable liquid phase (nanodroplets) is hypothesized to improve penetration into biofilms due to their smaller size (0.1 to 0.4 mm in diameter) (107). Upon ultrasound activation, nanodroplets expand into microbubbles, creating shear stress from inside the biofilm ( 108).…”
Section: Solutionsmentioning
confidence: 99%
“…Upon ultrasound activation, nanodroplets expand into microbubbles, creating shear stress from inside the biofilm ( 108). This experimental treatment strategy has successfully improved antibiotic efficacy against S. aureus biofilms in vitro (107,108), improved transdermal drug delivery (109), and transiently permeabilized the blood brain barrier (110); in theory, this method could be expanded to improve drug penetration to any niche that is vascularized. In addition, it has the potential for rapid clinical translation, as ultrasound is already used routinely in wound debridement, some nanodroplet formulations are variants of FDA-approved ultrasound contrast agents that are already in clinical practice (111), and the low-pressure ultrasound settings required can be achieved with existing ultrasound hardware at pressures below the FDA set limits for diagnostic imaging (107).…”
Section: Solutionsmentioning
confidence: 99%